Do algorithm traders mitigate insider trading profits?: Evidence from the Thai stock market - Wongsinhirun, Nopparat; Chatjuthamard, Pattanaporn; Treepongkaruna, Sirimon; Likitapiwatc, Tanakorn (PloS one, 2021)
This paper asks whether algorithm traders (AT) mitigate insider trading profits in the Thai stock market over the period of 2010–2016. We find that in general it does but not in the case of buy side, big trades nor the executive trades. Our findings suggest that, to some extent, AT can take important role to increase an efficiency in stock market by processing the public information and incorporating it into price at ultra-fast speed. Additional robustness checks based on the instrumental variable approach confirm our findings.